L’essor de l’industrie pétrochimique en Arabie Saoudite - Hambleton, H. (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTEight giant petrochemical joint ventures will come on stream in Saudi Arabia between 1983 and 1985, reaching full capacity by 1987. While the equity for these complexes will be at least $12 billion, they will benefit from very cheap feedstock making them highly competitive. With the foreign partners in the ventures marketing much of the output abroad and with a growing domestic demand, there should be little difficulty with sales. In any event Saudi Arabia can link the sale of petrochemicals with the availability of crude oil. A re-structuring of the world production of petrochemicals is virtually inevitable, with Saudi Arabia and other countries with cheap feedstock producing bulk petrochemicals while the more industrialized countries concentrate on specialty petrochemicals with a greater value-added. Quebec, with petrochemicals a growth sector, is well placed to take advantage of these changes. Saudi Arabia, which normally runs a substantial trade surpluses with Quebec—some $360 million in 1981—might well opt to invest part of theses surpluses in a petrochemical industry in Quebec.